Fasting and postprandial conditions affect both fatty acids and lipid compositions in the hypothalamus and fat-soluble vitamins in the serum of male rats - Dayangac, Alpaslan; Gosselink, Kristin Leigh; Yilmaz, Okkes (Brill, 2012)
The purpose of this study was to examine the effects of fasting and re-feeding on lipid derivative patterns in the hypothalamus, and on vitamin, cholesterol and malondialdehyde (MDA) levels in serum. Adult male Wistar albino rats were assigned (n = 6/group) as follows: normally-fed controls (CON), fasted for 24 h (24F). fasted for 48 h (48F), and fed normally for 2 d after fasting for 48 h (FAF). Biochemical measures were analyzed by gas chromatography (GC) and high performance liquid chromatography (HPLC). Our results demonstrate that hypothalamic saturated fatty acid (C16:0, C18:0) levels were lower, and unsaturated fatty acid (C22:6 n-3, C22:4 n-6, C20:4 n-6) levels were higher. in the 48F and FAF groups than in CON (P < 0.01). In addition, hypothalamic monounsaturated fatty acid (MUFA) levels were lower, and polyunsaturated fatty acids (PUFA) levels were higher, in 24F than in CON. Total hypothalamic lipids in both 24F and 48F were higher than CON, and cholesterol was elevated in the hypothalami of all experimental groups as compared to CON. Serum malondialdehyde was higher in fasted and FAF groups; 24F and 48F also had higher serum cholesterol levels, than CON (P < 0.01, P < 0.001). Serum alpha-tocoferol, retinol and vitamin C values were lower in 48F than CON (P < 0.05). In conclusion, we demonstrate that feeding state can significantly alter brain fatty acid and lipid derivative levels, and serum concentrations of cholesterol and vitamins. These changes may consequently influence lipid peroxidation, fatty acid synthase or desaturase system in hypothalamic fields. (C) Koninklijke Brill NV, Leiden, 2012.
Keywords: Fasting: fatty acids; fat-soluble vitamins; hypothalamus; malondialdehyde; rat